2019
DOI: 10.1364/josab.36.00a131
|View full text |Cite
|
Sign up to set email alerts
|

Directional supercontinuum generation: the role of the soliton

Abstract: In this paper we numerically study supercontinuum generation by pumping a silicon nitride waveguide, with two zero-dispersion wavelengths, with femtosecond pulses. The waveguide dispersion is designed so that the pump pulse is in the normal-dispersion regime. We show that because of self-phase modulation, the initial pulse broadens into the anomalous-dispersion regime, which is sandwiched between the two normal-dispersion regimes, and here a soliton is formed. The interaction of the soliton and the broadened p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…We see that, to realize the manipulation of a signal pulse by (3+1)D probe LB, a very low input light power is needed, which is due to the resonance character and the double EIT effect in the system. This is very different from conventional optical media, such as glass-based optical fibers, where picosecond or femtosecond laser pulses are usually needed to reach a high power to produce a sufficiently nonlinear effect needed for the formation of an optical soliton [6][7][8][9][10][11][12][13][14].…”
Section: Manipulation Of a Signal Pulse By (3+1)d Lb And Their Trajecmentioning
confidence: 96%
See 1 more Smart Citation
“…We see that, to realize the manipulation of a signal pulse by (3+1)D probe LB, a very low input light power is needed, which is due to the resonance character and the double EIT effect in the system. This is very different from conventional optical media, such as glass-based optical fibers, where picosecond or femtosecond laser pulses are usually needed to reach a high power to produce a sufficiently nonlinear effect needed for the formation of an optical soliton [6][7][8][9][10][11][12][13][14].…”
Section: Manipulation Of a Signal Pulse By (3+1)d Lb And Their Trajecmentioning
confidence: 96%
“…The principle is that a high intensity laser light transfers some of its momentum to small particles and hence a force acts on the particles, which has significant applications in many research fields [2][3][4][5]. In recent years, much attention has been focused on soliton-radiation trapping (i.e., trapping light by light) in many nonlinear optical media through cross-phase modulation (CPM) effect, which have led to the observation of the Raman-induced frequency shifts and supercontinuum generation [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In this region, solitons are generated and later break into fundamental solitons, accompanied by the emission of dispersive wave into normal dispersion domains as shown in Fig. 4c 29,30 . This mechanism explains the successive emission of DW 1 and DW 2 in normal dispersion.…”
Section: Pulse Evolutionmentioning
confidence: 99%
“…However, recent investigations have revealed that dispersive waves can also be emitted when the input pulse is pumped under normal group velocity dispersion (GVD). Due to strong self-phase modulation (SPM), the input pulse can extend from normal dispersion to anomalous dispersion, forming solitons that emit dispersive waves in the normal dispersion region 29,30 . Furthermore, non-soliton pulses propagating under normal dispersion…”
mentioning
confidence: 99%
“…In addition, it is preferable to choose materials with a large Kerr nonlinearity [8] since SC generation is typical nonlinear interaction processes including self-phase modulation, cross-phase modulation, soliton dynamics, Raman scattering, four-wave mixing, and so on. [9,10] ChGs have emerged as promising nonlinear materials with a number of distinct properties that make them attractive for mid-IR applications, ChGs consist of one or more of chalcogen elements S, Se, and Te that are covalently bonded with glass forming materials such as As, Sb, Ge, and Ga. [11] Compared to other glass materials, ChGs exhibit higher optical Kerr nonlinearity, high refractive index, and wide mid-infrared transparency window. [12] ChGs can provide a wide infrared transmission spectrum with sulfides exceeding 8.5 µm, selenides up to 14 µm, and tellurites to around 20 µm.…”
Section: Introductionmentioning
confidence: 99%